Can Someone Become A Counselor To Gain The Target Towards An Islamic Education Counseling? - Eka Damayanti; Nurqadriani Nurqadriani; Syarifuddin Ondeng; Muh Yahdi; Muthmainnah Muthmainnah (At-Tarbiyat, 2021)
Humans in the present day are capable of encountering complicated challenges, as well as the complexity of the times. Based on the Qur'an and Hadith, the existence of Islamic Education counseling is a solution in helping individuals get through their difficulties. The purpose of this paper is to discuss human potential as counselors and targets of Islamic education counseling from a scientific standpoint. This article arose through literature review that included data from books, scientific journals, including research papers. Content analysis was used to examine the data. The results demonstrated that Islamic education counseling could make it easier to find alternative problem-solving methods based on the Qur'an and Hadith, and also faith in Allah SWT. Islamic education counseling encourages clients to further strengthen their natural personality so that they will always carry out Allah SWT's commands, and indeed the presence of Islamic education counseling can increase the counselee's faith, Islam, and sincerity to become human beings.